An open access 90 m resolution VS data and map for areas affected by the January 2025 M6.8 Dingri Xizang, China earthquakeKey points - Jian Zhou; Li Li (Earthquake Science)
In this study, we developed a high-resolution (3 arcsec, approximately 90 m) VS map and associated open-access dataset for the 140 km × 200 km region affected by the January 2025 M6.8 Dingri Xizang, China earthquake. This map provides a significantly finer resolution compared to existing VS maps, which typically use a 30 arcsec grid. The VS values were estimated using the Cokriging-based VS proxy model (SCK model), which integrates VS measurements as primary constraints and utilizes topographic slope as a secondary parameter. The findings indicate that the VS values range from 200 to 250 m/s in the sedimentary deposit areas near the earthquake’s epicenter and from 400 to 600 m/s in the surrounding mountainous regions. This study showcases the capability of the SCK model to efficiently generate VS estimations across various spatial resolutions and demonstrates its effectiveness in producing reliable estimations in data-sparse regions.